Life Values Among Lebanese and Portuguese College Students: A Cross-Cultural Comparison - Marques, Cátia; do Céu Taveira, Maria; El Nayal, Mayssah; Silva, Ana Daniela; Gouveia, Valdiney (Journal of International Students, 2020)
This study aims to test the applicability of the functional theory of life values and score differences among a group of students from Lebanon and Portugal. Participants include 565 college students—278 Lebanese and 287 Portuguese. A demographic questionnaire and an adapted version of the Basic Values Survey were completed. Confirmatory/multigroup factor analysis, a generalized Procrustes analysis, and a t test were used. Results indicate that content and structure hypotheses were equivalent among the two groups. There were significant differences between the Lebanese and Portuguese students in normative and promotion values in favor of the first group, and in interactive, suprapersonal, and excitement values in favor of the second. This study has implications for institutional academic and social practices with international college students.